2019
DOI: 10.1038/s41598-019-48563-w
|View full text |Cite
|
Sign up to set email alerts
|

Ejaculate testosterone levels affect maternal investment in red junglefowl (Gallus gallus gallus)

Abstract: Substantial concentrations of testosterone are not only present in a male’s circulation, but also in its ejaculate. Surprisingly, the regulation of ejaculate T and its effects on females and their offspring, potentially a cryptic paternal trait, are not known. We found lower circulating and higher ejaculate T concentrations in subordinate red junglefowl ( Gallus gallus gallus ) males compared to dominant males, suggestive of an adaptive trade-off in T allocation to circulation and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
2
10
1
2
Order By: Relevance
“…The current study is based on our previous studies summarized in Table 1. In one previous study, (Lelono et al, 2019), we found that large-comb males are always winners in a confrontation with smallcomb males and after the social challenge have higher plasma T and lower ejaculates T compared to the subordinate males. However, whether these differences already existed before fight, for example related to the social status or physical characters such as body mass and comb size, or are due to winning or losing a fight remains to be tested.…”
Section: Introductionmentioning
confidence: 44%
“…The current study is based on our previous studies summarized in Table 1. In one previous study, (Lelono et al, 2019), we found that large-comb males are always winners in a confrontation with smallcomb males and after the social challenge have higher plasma T and lower ejaculates T compared to the subordinate males. However, whether these differences already existed before fight, for example related to the social status or physical characters such as body mass and comb size, or are due to winning or losing a fight remains to be tested.…”
Section: Introductionmentioning
confidence: 44%
“…The concentration of testosterone in seminal plasma was approximately two times less than in blood in both turkey [60] and chicken [61]. Seminal plasma testosterone concentration shows an inverse relationship with social status and blood plasma testosterone concentrations in red jungle fowl [62]. Testosterone concentrations in seminal plasma from ductus deferens and ejaculated seminal plasma are not significantly different [60,61].…”
Section: Hormonesmentioning
confidence: 86%
“…The seminal plasma is a complex mixture of proteins, free amino acids, lipids, carbohydrates, and hormones [ 5 , 20 , 21 , 22 , 23 , 24 ]. In the second experiment, it was decided to remove the seminal plasma because other studies reported a deleterious effect in the storage of semen samples of chicken and turkey [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the seminal plasma may have some components that protect of cryoinjury and improve the sperm resistance to cold-shock damage [ 16 , 17 , 18 ], but in some species (e.g., goat) the seminal plasma removal is routine in sperm cryopreservation protocols, because contains components that reduces the chances of efficient sperm preservation [ 19 ]. Some of these components include proteins, ions, free amino acids, lipids, carbohydrates, polyamines, steroid hormones, and prostaglandins [ 5 , 20 , 21 , 22 , 23 , 24 ]. The role of seminal plasma on bird semen in vitro storage remains largely a matter of speculation as both inhibitory and stimulating effects have been found [ 20 ].…”
Section: Introductionmentioning
confidence: 99%